The Role of Ferroptosis in Acute Kidney Injury - Zhang, Jinshi; Wang, Binqi; Yuan, Shizhu; He, Qiang; Jin, Juan (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is a novel cell death method discovered in recent years. It is usually accompanied by massive accumulations of iron and lipid peroxidation during cell death. Recent studies have shown that ferroptosis is closely associated with the pathophysiological processes of many diseases, such as tumors, neurological diseases, localized ischemia-reperfusion injury, kidney injury, and hematological diseases. How to intervene in the incidence and development of associated diseases by regulating the ferroptosis of cells has become a hot topic of research. This article provides a review of the role of ferroptosis in the pathogenesis and potential treatment of acute kidney injury.